PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN RODA BACA PINTAR PADA MEMBACA PERMULAAN SISWA KELAS 1 DI SDN CILEGON X - Hikmawati Hikmawati; Odin Rosyidin; Rina Yuliana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to develop Papan Roda Baca Pintar media, to reveal the feasibility of Papan Roda Baca Pintar Media and the students’ response after using Papan Roda Baca Pintar Media in learning early reading. The research method used was research and development adapting and modifying Borg and Gall research model which consisted of 6 stages of research; they were problem analysis, data collection, product design, design validation/expert testing, design revision, and product testing/limites trials. The product was tested to students door to door, with the permission of the teacher. The product feasibility was based on the assessment results from material experts, linguists, media experts, and students’ response questionnaires. Data were collected through questionnaires, observations, and documentations. The results of research and development showed that after a series of trials, questionnaires, amd experts’ validations, Papan Roda Baca Pintar media was very feasible. Based on the assessment from material experts, the percentage was 94% with a very feasible category while the percentage from the linguists’ assessment was 71% with a feasible category. After that, the result from the media experts was 85% in the very feasible category, and the last, the result from limited trials (response questionnaires) was 95% which was also in the very good category on the Likert Scale. This result was interpreted by the feasible test and the result was very feasible.